(untitled) (Revista Internacional de Formação de Professores, 2016)
I pose in this article a review of the working conditions of teachers in what I have called the school hegemonic order. This is placed in relation to the neoliberal and neoconservative proposal that colonizes the various spaces of the school. Faced with this scenario I state the need to move by a new counter-hegemonic school order, democratic, to recover the right to education and sovereignty as essential axes. I point some lines from which to understand the logic of school transformation.